Eksekusi Hak Tanggungan dalam Perjanjian Pembiayaan - Sobirin, Sobirin; Abdullah, Junaidi (Sharia Faculty Islamic Economic Law Study Department, 2019)
BMT both in the form of KJKS and KSPS in providing loans and financing can be in the form of Mudhorobah, Murobahah or Musyarokah, usually KJKS and KSPS parties make the conditions in the form of collateral. Goods that are used as collateral can be in the form of movable or immovable objects. When collateral is in the form of a moving object (usually in the form of a motorcycle or car), the KJKS and KSPS will make a fiduciary guarantee and when the collateral is in the form of immovable property (usually in the form of land or house), the KSPS and KJKS will dependents. When a member who carries out a broken promise, the KSPS Logam Mulia party can execute directly the Underwriting Right object. However, the KSPS Logam Mulia sub-district of Klambu, Grobogan, did not directly execute the object of collateral rights. The mortgages in the KSPS Logam Mulia sub-district in Klambu, Grobogan Regency were carried out to bind the collateralized object to guarantee the immovable property such as land or land along with the building on it. KSPS Logam Mulia does not execute directly on objects that are pledged as collateral rights, but through sales voluntarily or ask for help to sell.